ROOT CANAL TREATMENT WITH FIBER POST AND JACKET CROWNS RESTORATION POST TRAUMA MAXILLARY CENTRAL INCISOR - Christina Mahardika; Maghfira Devega; Muhamat Muhtar S Abdurrohman (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: The maxillary permanent central incisors are the anterior teeth most at risk of experiencing tooth fracture injuries due to trauma. Dental trauma is caused by impact resulting from sufficient mechanical energy to involve the exposed pulp. Appropriate therapy for technical ability to restore teeth due to trauma with exposed pulp with root canal treatment accompanied by fiber post restoration and jacket crown. Case report: a 22 year old male patient diagnosed with pulp necrosis accompanied by asymptomatic apical periodontitis and root canal treatment was performed on the upper right central incisor. Objective examination results showed negative vitality and positive percussion. The results of the radiological examination showed a radiolucent area in the apical area and a widened periodontal membrane in the apical 1/3 of the tooth. The tooth undergoes root canal treatment by isolating the working area, then preparing the access cavity. Negotiate the root canal using #10 K-files and measure the working length with an apex locator. The root canal was irrigated using 2.5 % NaOCl followed by 17% EDTA. and 2% chlorhexidine. Preparation is carried out using hand-held instruments. Filling the root canal with endomethasone sealer using the lateral condensation obturation technique and followed by making a fiber post restoration and Porcelain Fused Metal crown at the next visit. Conclusion: Root canal treatment in the case of the upper right central incisor with a fused metal porcelain jacket crown restoration and fiber post which was carried out in this case showed clinical and radiological success